Analysis of the CC–CV Charging Profile Influence on Electric Vehicle Battery Lifespan - Văn Ánh Dương; Phạm Thanh Tuân; Dương Tuấn Tùng; Nguyễn Hoàng Duy Tân; Nguyễn Tiến Thắng (Journal of Technical Education Science, 2026)
Batteries represent a critical and high-value component within modern energy systems, particularly in the domain of electric vehicles (EVs). The operational lifespan of batteries significantly influences overall system performance, reliability, lifecycle costs, and environmental sustainability. Among the various stressors affecting battery health, the charging process is recognized as a predominant contributor to electrochemical degradation. Adverse conditions such as elevated charging rates, non-optimal ambient or cell temperatures, and suboptimal state-of-charge (SoC) windows can accelerate capacity fade and internal resistance growth, thereby diminishing battery longevity. Despite substantial advancements in battery technology, accurately characterizing and quantifying the long-term effects of diverse charging parameters remains a complex challenge, necessitating advanced modeling. In this context, the authors conducted comprehensive simulations to evaluate battery degradation behavior under varying charging profiles and environmental conditions. Based on the simulation outcomes, the study proposes evidence-based strategies to assist EV users in optimizing charging protocols, ultimately enhancing system efficiency, reducing maintenance costs, and prolonging battery service life.